2014
DOI: 10.1017/s0950268813003208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meteorological factors on scrub typhus in a temperate region of China

Abstract: Scrub typhus is emerging and re-emerging in many areas: climate change may affect its spread. To explore the effects of meteorological factors on scrub typhus, monthly cases of scrub typhus from January 2006 to December 2012 in the Laiwu district of temperate northern China were analysed. We examined the correlations between scrub typhus and meteorological factors (and their delayed effects). We built a time-series adjusted negative binomial model to reflect the relationships between climate variables and scru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 32 publications
12
48
0
1
Order By: Relevance
“…While high atmospheric pressure is thought to be adverse to mites’ survival [9]. The time lags in the effect of meteorological factors may be related to the life cycle of chigger mites as about 2–3 months [12] and the incubation period of the disease (mean of 10–12 days) [11]. Because of the nature of that a chigger normally feeds on its host only once in its life cycle and the infection transmitted by a chigger must have been derived from the female parent by transovarian transmission [12, 25], the infection rate and population density of larval trombiculid mites largely depend on those of the last generation and the habitat during the time between egg hatch and settling down on a host for a larvae, which are influenced by relative humidity and atmosphere pressure in previous about 1–2 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While high atmospheric pressure is thought to be adverse to mites’ survival [9]. The time lags in the effect of meteorological factors may be related to the life cycle of chigger mites as about 2–3 months [12] and the incubation period of the disease (mean of 10–12 days) [11]. Because of the nature of that a chigger normally feeds on its host only once in its life cycle and the infection transmitted by a chigger must have been derived from the female parent by transovarian transmission [12, 25], the infection rate and population density of larval trombiculid mites largely depend on those of the last generation and the habitat during the time between egg hatch and settling down on a host for a larvae, which are influenced by relative humidity and atmosphere pressure in previous about 1–2 months.…”
Section: Discussionmentioning
confidence: 99%
“…Two-sided p -values under 0.05 were considered statistically significant. Considering that the mean incubation period of scrub typhus in humans is 10–12 days [11] and that the life cycle of chigger is several months [12], we first examined possible time lags of the influence of each meteorological factor (0–3 months) on monthly incidence of scrub typhus. The most significant lag was then used in the negative binomial regression.…”
Section: Methodsmentioning
confidence: 99%
“…Recent epidemiological data available in various resources (S1 Table), clearly demonstrates the gradual emergence of scrub typhus in several endemic countries (Fig 1). Even though the increasing number of reported cases of scrub typhus might be partly due to increased awareness and better surveillance systems in the developing countries [2,9], environmental change and human activity might be important factors contributing to the emerging trend [1417]. Given that vector mites maintain the intracellular pathogen, ecological changes of the vector species in local endemic regions could be the primary cause of the emergence of scrub typhus, as recently observed in South Korea [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Their density fluctuations are closely related to the seasonal distribution of scrub typhus cases, and the monthly distribution of scrub typhus cases was consistent with the fluctuation of Leptotrombidium scutellare[9, 30, 31]. Third, some studies have shown that meteorological factors affect the incidence of scrub typhus, such as temperature, sunlight, precipitation, etc[16, 32, 33]. The climatic conditions of Shandong Province from September to November may be most suitable for the occurrence of scrub typhus.…”
Section: Discussionmentioning
confidence: 70%